Analisis Peran Kegiatan Ekstrakurikuler PASKIBRA dalam Meningkatkan Kedisiplinan Remaja - Asiah Asiah; Irdah Fadila Rahmah Nst (Universitas Negeri Medan, 2025)
This study aims to find out how the role of extracurricular activities PASKIBRA contributes to enhancing the discipline of teenagers at State Senior High School 18 Medan and to understand the role of guidance counselors in supporting extracurricular activities. The problem formulation in this research is how the role of extracurricular activities PASKIBRA improves the discipline of students at the school and how the role of guidance counselors assists in extracurricular activities. This research uses a qualitative approach with descriptive qualitative research methods. The subjects in this study were selected using purposive sampling technique. The selected subjects are individuals involved in extracurricular activities at State Senior High School 18 Medan who can provide information, such as the Principal, the Vice Principal of Student Affairs, the PASKIBRA coaches and alumni, guidance counselors, class supervisors, and PASKIBRA members. The findings of the research indicate that the extracurricular activity of PASKIBRA plays a relevant role in improving the discipline of adolescents. Adolescents involved in the PASKIBRA extracurricular activity exhibit a higher level of discipline compared to other extracurricular activities or to those who do not participate in any extracurriculars at all. The forms of discipline observed among PASKIBRA members include time discipline, study discipline, etiquette discipline, and dress discipline. Support from various parties is crucial for the smooth running and success of this activity. The steps taken to enhance discipline vary, ranging from habituation, exemplification, to supervision. The guidance and counseling teacher also plays an important role in improving adolescent discipline. The guidance counselor actively provides assistance, direction, and motivation to encourage the youth.